2012
DOI: 10.1145/2337542.2337560
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Architecture for Learning Complex Problem-Solving Techniques from Demonstration

Abstract: We present a novel ensemble architecture for learning problem-solving techniques from a very small number of expert solutions and demonstrate its effectiveness in a complex real-world domain. The key feature of our "Generalized Integrated Learning Architecture" (GILA) is a set of integrated learning and reasoning (ILR) components, coordinated by a central meta-reasoning executive (MRE). The ILRs are weakly coupled in the sense that all coordination happens through the MRE. Each ILR learns independently from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…GILA (Generalized Integrated Learning Architecture) [51] is based on the combined use of several heterogeneous and independent problem-solving and learning methods, using an ensemble architecture in which a central metareasoning executive (MRE) controls the processing. It is aimed at addressing problems in difficult real-world domains, where tasks are complex with multiple interacting subproblems, and where near-optimal solutions are called for.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%
“…GILA (Generalized Integrated Learning Architecture) [51] is based on the combined use of several heterogeneous and independent problem-solving and learning methods, using an ensemble architecture in which a central metareasoning executive (MRE) controls the processing. It is aimed at addressing problems in difficult real-world domains, where tasks are complex with multiple interacting subproblems, and where near-optimal solutions are called for.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%
“…Different from classical ensemble learning, deep ensemble learning tries to tackle the problem of multimodal analysis and extends the bound of generalization ability of the ensemble learner. A key advantage of deep ensemble learning is that deep models can be used as base learners, which extends the representation capability to a great extent [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Chung and Sang [2000], memory based reasoning (MBR) and neural network (NN) learning are combined for yield improvement and an integrated framework is proposed for a yield management system based on hybrid machine learning techniques. In Zhang et al [2012], a set of heterogeneous independent learning components were coordinated by a central metareasoning executive. It has been demonstrated that machine learning techniques assist in managing complexity, diversity, and uncertainties in manufacturing process management [Monostori 2003].…”
Section: Introductionmentioning
confidence: 99%